Pengaruh Perencanaan Pajak dan Pajak Tangguhan Terhadap Kinerja Keuangan - Lulu Nailufaroh; Dien Sefty Framita; Riski Maulana (Universitas Serang Raya, 2023)
This study aims to examine and obtain empirical evidence regarding the effect of Tax Planning and Deferred Tax on Financial Performance in Manufacturing Companies in the Consumer Goods Industry Sector. Tax is one of the important sources for state revenue to finance state development. This study also discusses deferred tax and tax planning that will be carried out by the company in generating profits by looking at the financial performance of the company. This study uses a sample of 13 Manufacturing Companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange in 2017-2021. Data were collected using purposive sampling method and hypothesis testing using multiple linear regression. The dependent variable in this study is financial performance, while the independent variables in this study are tax planning and deferred tax. Based on the results of data analysis, it shows that tax planning has a positive effect on financial performance and deferred tax also has a negative effect on financial performance.